The effect of siblings and family dog ownership on children's independent mobility to neighbourhood destinations. (15th May 2016) - Christian, Hayley E.; Villanueva, Karen; Klinker, Charlotte D.; Knuiman, Matthew W.; Divitini, Mark; Giles‐Corti, Billie
Abstract: Objective : To investigate the effect of sibling age, gender and dog ownership on children's independent mobility and how this varies according to the destination visited. Methods : Parents reported whether their child had an older sibling; if the child and older sibling were of the same gender; the number of older siblings; if they owned a dog; and whether their child was allowed to independently travel to school, friends' or family house, park/oval/sporting field and local shop. Data were analysed for 181 children aged 8–15 years. Results : The strongest significant sibling effect for independently mobility to school, local shop and ≥3 destinations was for having an older sibling of the same gender ( p ≤0.05). For independent mobility to a friend's house and park, the strongest significant sibling effect was for having one older sibling ( p ≤0.05). Dog ownership was associated with increased odds of being independently mobile to ≥3 destinations (OR=2.43; 95%CI=1.03–5.74). Conclusions : Parents may be more likely to grant children licence to travel to local places if they are accompanied by an older sibling or the family dog. Implications : Understanding the effects of siblings and dog ownership on children's independent mobility will assist in identifying strategies through which independent mobility can be encouraged.